Pregnancy, Pancreatitis, and Hypoglycemia: Multi-modal Management in a Case with Multiple Endocrine Neoplasia-1 Syndrome - Anshita Aggarwal; Aditya Dutta; Sanjay K. Bhadada; Anil Bhansali; Dandan Shi (Wolters Kluwer Health, 2021)
Abstract. A 32-year-old lady presented to us at 6 months of gestation with acute pancreatitis due to parathyroid hormone-dependent hypercalcemia and with insulin-dependent hypoglycemia, owing to parathyroid adenoma and possibly insulinoma, respectively. The parathyroid adenoma was localized on the magnetic resonance imaging of the neck; however, imaging for the insulinoma could not be done due to the gravid state. Due to the simultaneous occurrence of tumours in two endocrine glands, namely, parathyroid gland and pancreatic islet cells, a diagnosis of MEN-1 (multiple endocrine neoplasia) was considered, which is very rarely seen in pregnancy. Her hypercalcemia was effectively managed with cinacalcet and alcohol ablation of the parathyroid adenoma while her hypoglycemic episodes were managed with short and long-acting octreotide injections during the antenatal period. She had a full-term cesarean delivery, with no maternal or neonatal complications, except for transient neonatal hypoglycemia. The patient was followed up for 1 year after her delivery with no further episodes of hypercalcemia and hypoglycemia, on medical management. Tc99m sestamibi scan was done after delivery which confirmed the presence of a left inferior parathyroid adenoma. MEN-1 with pregnancy thus poses a diagnostic and therapeutic challenge and our case highlights the role of multimodal medical therapy for successful management.